2012
DOI: 10.1016/j.yebeh.2012.08.031
|View full text |Cite
|
Sign up to set email alerts
|

A critical and descriptive approach to interictal behavior with the Neurobehavior Inventory (NBI)

Abstract: Depression influences NBI scoring, mainly emotionality and hyposexuality traits. Neurobehavior Inventory subscales can be better interpreted with an appropriate evaluation of comorbid mood and anxiety disorders. Compromise in left temporal mesial structures is associated with increased tendency toward sad affect, whereas right temporal pathology is associated with increased beliefs in personal destiny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…A total score of 20 or more affirmative statements and three or more positive answers in each subscale determine the existence of the characteristic [11]. Neurobehavior Inventory traits will be classified according to de Oliveira et al [7], which are included in Table 1 showing NEO-PI-R and NBI contents.…”
Section: Instrumentsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total score of 20 or more affirmative statements and three or more positive answers in each subscale determine the existence of the characteristic [11]. Neurobehavior Inventory traits will be classified according to de Oliveira et al [7], which are included in Table 1 showing NEO-PI-R and NBI contents.…”
Section: Instrumentsmentioning
confidence: 99%
“…The sense of personal destiny, seriousness, religious conviction, writing tendency, and cosmic interest were significantly elevated in MTLE/HS while in JME, higher scores were found in anger and temper, dependency, emotion, and somatic complaints. De Oliveira et al [7] identified three main components in NBI corresponding to features related to Gastaut-Geschwind syndrome: emotions (Factor 1), hyposexuality (Factor 2), and unusual ideas (Factor 3). In our JME group, higher scores were observed in traits of Factor 1 while in MTLE/HS, traits of Factor 3 were more elevated.…”
Section: Nbi Traitsmentioning
confidence: 99%
See 3 more Smart Citations